Evaluation of the effectiveness of revealing of reserves of production in the agricultural sector - Zhaksybayev, K.R.; Yeskerova, Z.A. (BUKETOV BUSINESS REVIEW, 2018)
This article discusses the possibility of determining the marginal product in a multi-factor production functions, the relationship of the distribution of the total social product. A purposeful study of the factors in the process of economic analysis allows to reveal reserves of production, as in every trade there are some unused opportunities to improve production efficiency, improve quality, improve the work. They are called reserves and production are divided into clear, visible, which only need to operate in the interests of production, and the hidden, reveal that by using techno-economic analysis, because such reserves are primarily untapped opportunities as factors. The article also considers socio-economic resources associated with the improving economic and moral incentives, to improve the conditions and content of work, using human factor, strengthening of the role of labor collectives in the organization and management of production. At the present stage of market transformations the special importance of maximizing the potential for improving the efficiency of production depends on what is changing are the main factors of economic growth.